REFORMS IN THE DEVELOPMENT OF SECTORS AND REGIONS OF THE DIGITAL ECONOMY (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
This article examines reforms aimed at the digital transformation of sectors and regions within the framework of the digital economy. The study analyzes digitalization strategies, their contribution to competitiveness, productivity growth, innovation development, and sustainable economic progress. Special attention is devoted to the experience of Uzbekistan, where large-scale reforms are being implemented under the Digital Uzbekistan–2030 strategy. The paper identifies the main achievements, challenges, and opportunities associated with digital transformation and proposes recommendations for improving regional and sectoral digital development.